Indeks Stakeholders Pengelolaan Daerah Aliran Sungai dengan Pendekatan KISS di Indonesia - Sriyana, Ignatius (Department of Civil Engineering, Diponegoro University, 2018)
Integrated watershed management (IWM) using KISS (coordination, integration, synchronisation, and synergy) method is believed to be the answer for problems lingering the integrated watershed management in Indonesia. How successful the management is depends on how capable of stakeholders are to performing coordination, integration, synchronisation, and synergy in managing the watershed. This study aimed at measuring the rates of coordination, integration, synchronisation, and synergy performed by each stakeholder by applying an